2021
DOI: 10.1186/s12879-021-06236-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of latent tuberculosis in patients with hematological neoplasms in a cancer referral hospital in Mexico City

Abstract: Objective To determine the prevalence of Latent Tuberculosis in patients with hematological neoplasms at the Instituto Nacional de Cancerología in Mexico City using the Tuberculin skin test (TST). Methods This retrospective study included all patients with a recent diagnosis of hematological neoplasms who were admitted for treatment from 2017 to 2018 and who were screened for latent tuberculosis with the TST. The prevalence of latent tuberculosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
4
1
Order By: Relevance
“…23 Outside the border region, the prevalence of LTBI in Mexico has been less studied, but still shows higher rates. 24,25 In the absence of a gold standard, it had been described that using both QFT and TST would increase the detection of LTBI in PLWHIV compared with TST alone; 26,27 our study showed an increase from 6.8% to 11.2%, similar to the findings of Kussen et al, 26 who reported an increase from 9% to 17%.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…23 Outside the border region, the prevalence of LTBI in Mexico has been less studied, but still shows higher rates. 24,25 In the absence of a gold standard, it had been described that using both QFT and TST would increase the detection of LTBI in PLWHIV compared with TST alone; 26,27 our study showed an increase from 6.8% to 11.2%, similar to the findings of Kussen et al, 26 who reported an increase from 9% to 17%.…”
Section: Discussionsupporting
confidence: 86%
“…2 To our knowledge, this is the largest cohort published in Mexican PLWHIV evaluating a real-life situation to improve LTBI detection. We found an LTBI prevalence of 11.2%, which is lower than the one reported in other cities in our country (31–57%); 5,23,24 this can be attributed to high-risk characteristics of their studied populations, such as a high proportion of injection drug users and female sex workers in Tijuana (U.S. border city) 5 or the migratory process from Latin America, that takes place in the US-Mexico border states; this region accounts for 30% of total reported TB cases among both countries. 23 Outside the border region, the prevalence of LTBI in Mexico has been less studied, but still shows higher rates.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…However, our cohort was considerably larger and was more homogenous as it involved only patients with acute leukemia. In contrast, Orsorio-Lopez and colleagues demonstrated a higher prevalence of 31.2% for LTBI infections when focusing primarily on non-Hodgkin’s and Hodgkin’s lymphoma patients who comprised 347 of 446 (77.8%) of the patients with hematologic malignancies [ 17 ]. They considered a positive TST to be 5 mm of induration and observed that 250 out of 446 (56.1%) patients were vaccinated for BCG [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“… 11 Elevated liver enzymes caused by INH therapy have been determined in various ways in the literature. Osorio-López et al 12 planned INH as LTBI treatment for 93 patients with HM for nine months, and they observed 15.1% of drug-related adverse effects. 4.3% of the patients had to discontinue the treatment due to side effects related to INH, and 3.2% (n=3) of them were due to elevated liver enzymes.…”
Section: Discussionmentioning
confidence: 99%